1999
DOI: 10.1002/(sici)1099-0690(199902)1999:2<431::aid-ejoc431>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Access to 4,5-Dinitro-1,3,5,7-octatetraene Systems

Abstract: The reactions between 1,4‐bis(diethylamino)‐2,3‐dinitro‐1,3‐butadiene (2), easily obtainable by ring‐opening of 3,4‐dinitrothiophene with diethylamine, and 2‐substituted vinylmagnesium bromides gave good yields of the 4,5‐dinitro‐1,3,5,7‐octatetraene derivatives 3a–e. With 1‐phenylmagnesium bromide, conversely, only 3,4‐dinitro‐1,4‐diphenyl‐1,3,5‐cyclooctatriene (4f) was obtained. From the unsubstituted dinitrooctatetraene 3a both the octatriene cycloisomer 4a and the valence tautomer of the latter (6a) could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…As already pointed out, the ring-opening of nitrothiophenes produces appealing building-blocks encompassing a number of versatile conjugated functionalities. A systematic exploitation of their synthetic possibilities began about fifteen years ago for the dinitrobutadienes 5 deriving from 3,4-DNT and only some ten years later for mononitrobutadienes deriving from 3-NT and other β-NT's (11). As far as building-blocks from 2-NT (9) are concerned, we are still at a very initial stage, but they seem to be as much promising as the others.…”
Section: Exploitation Of the Synthetic Potentialities Of Nitrobutadiementioning
confidence: 99%
See 1 more Smart Citation
“…As already pointed out, the ring-opening of nitrothiophenes produces appealing building-blocks encompassing a number of versatile conjugated functionalities. A systematic exploitation of their synthetic possibilities began about fifteen years ago for the dinitrobutadienes 5 deriving from 3,4-DNT and only some ten years later for mononitrobutadienes deriving from 3-NT and other β-NT's (11). As far as building-blocks from 2-NT (9) are concerned, we are still at a very initial stage, but they seem to be as much promising as the others.…”
Section: Exploitation Of the Synthetic Potentialities Of Nitrobutadiementioning
confidence: 99%
“…The synthetic potentialities offered by the ring-opening products 5 of 3,4-DNT have been extensively examined by us since 1990, and an overview of the main results so far obtained within the overall ring-opening / ring-closure protocol of Scheme 5 is depicted in Schemes 6A-6C. The initial step in the syntheses shown is always represented by the practically quantitative replacement of the two diethylamino groups by reaction with an organometallic compound, namely an aryl (Scheme 6A), 10 vinyl (Scheme 6B) 11 or benzyl Grignard reagent (Scheme 6C). 12 In the latter two cases, nitrosubstituted carbocyclic compounds have been eventually obtained, as the result of interesting processes encompassing electrocyclization steps followed or not by…”
Section: Synthetic Exploitation Of 14-bis(dialkylamino)-23-dinitro-mentioning
confidence: 99%
“…[1] In the present paper we report on the reactions of dinitrobutadienes 1 with some representative primary amines, a process leading to interesting pyrrolidine derivatives amenable to further transformations, e.g., into pyrrolines 3 and pyrroles 4 (Scheme 1). Scheme 1. i) RNH 2 (3.3 mol equiv.…”
Section: Introductionmentioning
confidence: 99%
“…In the frame of our studies on the synthetic exploitation of the ring-opening reactions of 3,4-dinitrothiophene and in particular of the ensuing 1,4-diaryl-2,3-dinitro-1,3-butadienes 1, we have shown that the two conjugated nitrovinyl moieties of 1 can be properly modified to furnish aliphatic and heterocyclic targets which are normally difficult to synthesise. [1] In the present paper we report on the reactions of dinitrobutadienes 1 with some representative primary amines, a process leading to interesting pyrrolidine derivatives amenable to further transformations, e.g., into pyrrolines 3 and pyrroles 4 (Scheme 1). Scheme 1. i) RNH 2 (3.3 mol equiv.…”
Section: Introductionmentioning
confidence: 99%